Assessing the effect of Augmented Reality on English language learning and student motivation in secondary education - Marrahi-Gomez, Victor; Belda-Medina, Jose (Frontiers in Education, 2024)
The integration of Augmented Reality (AR) in language learning has garnered attention in the field of education, yet its effectiveness in enhancing grammar proficiency among secondary school students remains relatively unexplored, especially given that previous research has predominantly focused on vocabulary acquisition at the primary and college levels. This study, based on a mixed-methods approach and convenience sampling, is aimed at assessing students' attitudes toward the integration of technology (H1) in language learning and examining the impact of using AR on grammar learning (H2) and motivation (H3) among secondary education students. Employing a mixed-method approach and convenience sampling, the research involved 130 students aged 14 to 15 from two secondary schools, divided into an experimental group (n=64) and a control group (n=66). Both groups received instruction on English comparative and superlative forms and completed a variety of exercises. The control group followed a traditional approach using a printed handbook, while the experimental group engaged with an AR-based lesson containing equivalent grammar activities and vocabulary in a multimedia format. Pre and post-tests were administered to evaluate grammar proficiency, accompanied by pre and post-surveys. Semi-structured discussion was used for the qualitative data. The findings revealed a strong interest in integrating AR technology into grammar learning, underscored by a positive attitude toward its implementation in secondary education. However, no statistically significant differences were detected in grammar learning performance between the two student groups. These findings emphasize the importance of providing proper teacher training in secondary education to effectively utilize AR technology and highlight the need for further research to explore its effectiveness and long-term impact. world environment to enhance the user's perception of reality. The prevalence of Software Development Kits (SDKs) such as ZapWorks, Roar, Augment, and ARkit Unity is steadily rising within various educational settings. These SDKs are employed to provide students with immersive experiences and enhance their performance, engagement, and motivation.